2003
DOI: 10.1530/rep.0.1250095
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental role of increased production of nitric oxide in lipopolysaccharide-induced embryonic resorption in mice

Abstract: Nitric oxide (NO) fulfils important functions during pregnancy and has a role in implantation, decidualization, vasodilatation and myometrial relaxation. However, at high concentrations, such as those that are produced in sepsis, NO has toxic effects as it is a free radical. The aim of this study was to characterize uterine and decidual NO production in lipopolysaccharide (LPS)-induced embryonic resorption in mice and to determine which isoforms of nitric oxide synthase (NOS) take part. LPS produced 100% embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(58 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…LPS has been associated with adverse pregnant outcomes in rodent animals. According to an earlier report, mice exposed to LPS at early gestational stage caused embryonic resorption [3]. We and others showed that mice exposed to LPS at late gestational stage resulted in fetal demise, intra-uterine growth restriction (IUGR), skeletal development retardation, and preterm delivery [4][8].…”
Section: Introductionmentioning
confidence: 97%
“…LPS has been associated with adverse pregnant outcomes in rodent animals. According to an earlier report, mice exposed to LPS at early gestational stage caused embryonic resorption [3]. We and others showed that mice exposed to LPS at late gestational stage resulted in fetal demise, intra-uterine growth restriction (IUGR), skeletal development retardation, and preterm delivery [4][8].…”
Section: Introductionmentioning
confidence: 97%
“…In human, Gram-negative bacterial infections are recognized as a cause of fetal loss and preterm labor [4], [5]. Mimicking maternal infection by exposing the pregnant rodents to LPS during the first trimester resulted in embryonic resorption and fetal death [6], [7]. Maternal LPS exposure during the second trimester caused fetal death and preterm delivery [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) plays important roles during pregnancy in implantation, decidualisation, vasodilatation of decidual, placental and uterine vessels and myometrial relaxation (Sladek et al 1997;Chwalisz et al 1999;Chwalisz and Garfield 2000;Ogando et al 2003). It has also been reported that NO participates in vascular invasion of the trophoblast (Ariel et al 1998) and infection control during pregnancy (Nowicki et al 1997).…”
Section: Introductionmentioning
confidence: 99%